Possible inflammatory responses in hypercholesterolemia patients receiving treatment using raw liquid extract of young cashew leaves in herbal homes in Nigeria - Olaniyan, Mathew Folaranmi; Ozuruoke, Donatus F.N.; Afolabi, Temitayo (International Journal of Health Sciences, 2018)
Objectives: The objective of this study was to determine the possible inflammatory responses in hypercholesterolemia patients receiving treatment using raw liquid extract of young cashew leaves in some herbal homes in Nigeria. Methods: Hypercholesterolemia patients (27: Aged 31–53 years; female - 10 and male - 17) 20 herbal homes in Saki-West, Saki-East, and ATISBO local governments constituting a Federal constituency in Nigeria, and non-hypercholesterolemia apparently healthy participants (50: Aged 20–64 years; female - 25 and male - 25) were recruited from the same federal constituency as test and control subjects, respectively. About 60 ml of this extract were given to the patients for an average of 14 days when there was a significant decrease in their plasma cholesterol. Plasma cholesterol was determined in the subjects using COBAS C111 auto chemistry analyzer; plasma tumor necrosis factor-alpha (TNF-α), interleukin (IL)-6, 8, and 29, intrahepatic chemokines such as fibrinogen and C-reactive protein (CRP), IL-6, CRP, hepatitis B surface antigen, antihepatitis C virus, and anti-human immunodeficiency virus were immunochemically determined by enzyme-linked immunosorbent assay, and identification of Plasmodium spp. was determined by microscopic examination of thick film-stained Giemsa stain. Results: There was a significant reduction in the plasma values of cholesterol, TNF-α, IL-6, and CRP with a significant increase in plasma aspartate transaminase (AST) and alanine transaminase (ALT). In the hypercholesterolemia patients who were supplemented with raw liquid extract of young cashew leaves compared with the control and their basal samples (P < 0.05). Discussion: Supplementation of raw liquid extract of young cashew leaves can cause a significant reduction in the plasma values of cholesterol TNF-α, IL-6, and CRP with an increase in plasma AST and ALT. In the hypercholesterolemia patients due to the phytochemicals in young cashew leaves.